Impact of solo surfacing on the value of the project (Research, Society and Development, 2019)
Soil sounding provides important information so that the structural calculator can devise a structure that specifically meets the requirements of each type of work; however, what happens in many cases (especially small works) is negligence with this type of information, since the owner claims that it is not financially viable to invest in such activity for various reasons. This neglect forces the calculator to take a more conservative posture, taking into account the security of its structure and thus generating in the vast majority of times an oversized structure, which increases the cost of this work. This paper analyzes between two works where one has a soil study and the other does not, using the standard penetration test (SPT) survey method. This paper aims to show the impacts of the SPT survey on the work and final project.